A radial basis function algorithm for simplified fluid-structure data transfer - Cordero-Gracia, M.; Gómez, M.; Valero, E. (International journal for numerical methods in engineering, 2014)
SUMMARYIn loosely‐coupled aeroelastic computation, the aerodynamic and elastomechanical models are based on different grids and eventually a simplified structural model, like a shell or stick, is considered. CFD tools are applied over the aerodynamic grid, whereas CSM tools are over the structural one. The meshes are usually non‐conforming; thus, three‐dimensional and non‐intrusive interpolation procedures are necessary to transfer structural deformations to the aerodynamic surface grid and aerodynamic loads to the structure. For that purpose, an interpolator based on radial basis functions has been developed. This tool does not require grid connectivities and can be applied to any three‐dimensional data.We have developed two strategies to deal with two special cases of interest. The first is when the structure is represented by a beam model and there is not a proper structural mesh close to the aerodynamic surface. The second is when managing a full configuration aircraft and the problem has been split into some small blocks in such a way that there are aerodynamic nodes belonging to more than one block. Copyright © 2014 John Wiley & Sons, Ltd.